VIRUS MOTORS RUNNING. (Communications of the ACM, 2005)
The article presents a discussion on computer viruses attacking vehicles. Car industry officials and analysts worldwide say it is only a matter of time before computer viruses become virulent in vehicles. Indeed, the growing interest in the hacker community in writing viruses for wireless devices puts auto-based computer systems at risk of infection. As carmakers adjust onboard computers to allow drivers to transfer information with MP3 players and mobile phones, they also make their vehicles more vulnerable to mobile viruses that jump between devices via the Bluetooth technology that connects them. The worst that could happen is the computer's control of engine performance and emissions, navigation, and entertainment systems ceases to function. Carmakers are taking the risk seriously, particularly since the first mobile phone virus--Cabir--spread through 20 countries using only Bluetooth.